XANTHUS OF LYDIA AND THE INVENTION OF FEMALE EUNUCHS*. (December 2015) - Matthews, Lydia
Abstract : Two fragments of the Lydiaca attributed to Xanthus of Lydia (mid fifth centuryb.c. ) preserve a curious claim that a king of Lydia (either the famous Gyges or the mythical Adramytes) was the first person to make eunuchs of women. In an attempt to make sense of these passages, it has been suggested that εὐνουχίζειν here refers not to castration, but rather to female genital cutting. If correct, this would provide our first evidence of this practice in Lydian culture or indeed anywhere in Anatolia. However, the assumption that what Xanthus describes somehow related to real practices is highly questionable. Instead, we should re-contextualize this story in terms of other fifth-century representations of luxury and eunuchs and in terms of Xanthus' own exemplary portraits of other Lydian kings.